THE INFLUENCE OF FAIRNESS PERCEPTION AND MOOD ON EMPLOYEE ORGANIZATIONAL CITIZENSHIP BEHAVIOR AT KPKNL MANADO - Piring, Reynold Gabriel (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2019)
Organizational Citizenship Behavior is very important for the discussion of human resources. The need for OCB in the company is to increase the productivity of coworkers, save the resources possessed by management and organizations, help to save more energy of a scarce resource for maintaining organization's functions, and can also be an effective means to coordinate work group activities, improve organizational capacity to retain the best employees, improve stability and ability to adapt to environmental changes. This research aims to find the influence of fairness perception and mood on employee organizational citizenship behavior at KPKNL Manado. This research is a quantitative research using multiple regression analysis. The number of sample used are 53 respondent which is the total employee of KPKNL Manado. The result shows that there is an influence of fairness perception and mood on organizational citizenship behavior at KPKNL Manado simultaneously, and there is an influence of fairness perception and mood on partially. It is recommended for future research to find out another variable that more able to influence organizational citizenship behavior at PT KPKNL Manado. Keywords: fairness perception, mood, organizational citizenship behavior